Digital Transformation in Guidance and Counseling Services and Its Implications for the Development of Pancasila-Based Student Character - Sabarrudin Sabarrudin; Nurul Faqih Isro’i (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Digital transformation in guidance and counseling (GC) services has emerged as a strategic response to the demands of 21st-century education, particularly in supporting the development of the Pancasila Student Profile. However, the integration of digital GC services with character development remains underexplored. This study aims to analyze the forms of digital transformation in GC services and examine their implications for the six dimensions of student character. A Systematic Literature Review (SLR) method was employed by systematically identifying, selecting, and analyzing relevant scholarly publications based on predetermined inclusion criteria. The data were synthesized thematically to identify patterns of implementation, contributions, and challenges in digital GC services. The findings reveal that digital GC services, including cyber counseling, Learning Management Systems (LMS), digital assessment tools, and interactive media, support students’ independence, critical thinking, creativity, and global diversity awareness through flexible access, reflective activities, and interactive engagement. However, the integration of spiritual, moral, and social collaborative values, particularly religiosity and gotong royong, remains limited. The main challenges include infrastructure disparities, limited digital competence among counselors, and concerns related to data security and privacy. This study concludes that digital transformation in GC services plays an important role in supporting student character development but requires a more integrative, value-based approach. The study contributes to the literature by proposing an integrative digital GC model that emphasizes value integration, data-driven personalization, and ethical, secure practices, while highlighting the need to strengthen counselor roles and supportive institutional policies.